2020
DOI: 10.4314/sajas.v50i1.10
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil type on density of trees and nutritive value of tree leaves in selected communal areas of South Africa

Abstract: This study aimed to describe the distribution and nutritive value of woody species growing in clay-loamy and red-brown sand from selected localities of North West, South Africa. Three 2.2 km transects, radiating from homesteads, which served as replicates, were established at each of four selected grazing areas. Nine 10 × 10 m homogenous vegetation units (HVU), 20 m apart, were marked in each transect. Woody plant density, height and canopy cover (CC), were recorded, and chemical properties and degradability v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…The nutritive content (Ash, CP, CF, ADL, NFC, DMD, DE and ME) in this study showed a wide significant variation among the browse species found in both soil types. These findings are consistent with Kraus et al [14] and Ravhuhali et al [2], who discovered that spatial variation has a great influence on the chemical composition of browse leaves. In this study, it was observed that the ash content from this study was higher in GM-L than AKS-CH, with a range between 35.7-136.7 g/kg DM.…”
Section: Chemical Composition Of Browse Speciessupporting
confidence: 92%
See 4 more Smart Citations
“…The nutritive content (Ash, CP, CF, ADL, NFC, DMD, DE and ME) in this study showed a wide significant variation among the browse species found in both soil types. These findings are consistent with Kraus et al [14] and Ravhuhali et al [2], who discovered that spatial variation has a great influence on the chemical composition of browse leaves. In this study, it was observed that the ash content from this study was higher in GM-L than AKS-CH, with a range between 35.7-136.7 g/kg DM.…”
Section: Chemical Composition Of Browse Speciessupporting
confidence: 92%
“…Browse tree species have long been considered important for livestock nutrition, particularly where the quantity and quality of feedstuff are limited for prolonged periods [1,2,42]. In this study, variations were observed among species and harvesting sites and the interaction between species and harvesting sites.…”
Section: Chemical Composition Of Browse Speciesmentioning
confidence: 78%
See 3 more Smart Citations